Cytotoxicity assessment of Multi-Walls Carbon Nanotubes (MWCNT) in secondary culture of Raw 264.7 Macrophages - Müller, Betina; Menezes, Patrick Flores; Silva, Luís Arthur Mendes da; Krause, Luciana Maria Fontanari; Silva, Solange Cristina da (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Nanotechnology has been developed rapidly in recent years, due to its applications in different sectors such as electronics, energy, and the pharmaceutical industry (DURAN et al., 2006; ANNON, 2011). Among the most widely used nanomaterials, carbon nanotubes (CNTs) stands out for their applications, such as drug carriers and biosensors and thus, its biocompatibility and toxicity should be studied. In this study, the cytotoxicity of multiple-wall carbon nanotubes (MWCNTs) in RAW 264.7 macrophages at concentrations of 1 and 5% of MWCNTs and 1 μg / ml of Escherichia coli lipopolysaccharide (LPS) was evaluated for 24 and 48 hours. Cytotoxicity was assessed by the release of lactate dehydrogenase (LDH), nitric oxide (NO) and gene expression of cytokines TNF-α and IL-1β. The results demonstrated that the MWCNTs at the concentrations that were used had no cytotoxic effect on the cells tested.